2011
DOI: 10.1371/journal.pone.0021768
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Xenograft Model in Zebrafish for High-Resolution Investigating Dynamics of Neovascularization in Tumors

Abstract: Tumor neovascularization is a highly complex process including multiple steps. Understanding this process, especially the initial stage, has been limited by the difficulties of real-time visualizing the neovascularization embedded in tumor tissues in living animal models. In the present study, we have established a xenograft model in zebrafish by implanting mammalian tumor cells into the perivitelline space of 48 hours old Tg(Flk1:EGFP) transgenic zebrafish embryos. With this model, we dynamically visualized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 29 publications
5
109
0
Order By: Relevance
“…The cell suspensions were implanted into each zebrafish embryo to create a tumor xenograft model in zebrafish (26). One day after implantation, SKLB646 and dasatinib were added directly into the fish water at different final concentrations.…”
Section: Transgenic Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell suspensions were implanted into each zebrafish embryo to create a tumor xenograft model in zebrafish (26). One day after implantation, SKLB646 and dasatinib were added directly into the fish water at different final concentrations.…”
Section: Transgenic Zebrafishmentioning
confidence: 99%
“…A tumor-induced neovascularization zebrafish model was further conducted to evaluate the effect of SKLB646 on angiogenesis in vivo (26). In the control group, endothelial cells were found to penetrate into the tumor tissue by two days after the implantation of tumor cells in zebrafish embryos, hence sustaining the tumor growth.…”
Section: Antiangiogenic Activity Of Sklb646 In Cultured Huvecs and Trmentioning
confidence: 99%
“…In some studies, some cancer cell lines are able to tolerate 28Ā°C Zhao et al 2009Zhao et al , 2011a. For the GBM cell line, U251, it has been demonstrated that varying the incubation temperature between 28Ā°C and 35Ā°C has no effect on the survival of cells after engraftment (Geiger et al, 2008).…”
Section: Growing Human Tumors Underwater: Approaches To Zebrafish Xenmentioning
confidence: 99%
“…We then used a tumor xenograft model in zebrafish, which was reported previously (34), to further evaluate the antiangiogenic effect of SKLB261. Briefly, red fluorescence-labeled B16 tumor cells were implanted into 48 hours postfertilization (hpf) embryos through the perivitelline space.…”
Section: Drug Studies In Zebrafishmentioning
confidence: 99%